2020
DOI: 10.1177/1758835920975356
|View full text |Cite
|
Sign up to set email alerts
|

Pooled analysis of 115 patients from updated data of Epitopes-HPV01 and Epitopes-HPV02 studies in first-line advanced anal squamous cell carcinoma

Abstract: Aims: The addition of docetaxel to cisplatin and 5-fluorouracil (DCF) has shown promising efficacy in advanced squamous cell carcinoma of the anus (SCCA). Preliminary results of Epitopes-HPV01 study showed a high rate of long-lasting complete response to DCF. The prospective, multicenter, Epitopes-HPV02 trial then confirmed the high efficacy of the modified DCF (mDCF) regimen in terms of complete response rate and long-term survival in metastatic or non-resectable locally advanced recurrent SCCA. Here, we pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 19 publications
(44 reference statements)
0
28
1
Order By: Relevance
“…In Epitopes-HPV02 study, a subgroup of 16 patients with synchronous metastases previously untreated, all patients presented an objective response after DCF with 56% of complete response of all involved sites including primary tumor [10]. The pooled analysis of Epitope-HPV01 and Epitopes-HPV02 studies confirmed these data [16]. None of the 29 patients with synchronous metastases presented a disease-progression at first evaluation during DCF administration, and the ORR was reached in 26 (89.7%) patients, including 16 (55.2%) patients with a complete response.…”
Section: Locally Advanced Disease: Time To Shift the Paradigm?mentioning
confidence: 61%
See 3 more Smart Citations
“…In Epitopes-HPV02 study, a subgroup of 16 patients with synchronous metastases previously untreated, all patients presented an objective response after DCF with 56% of complete response of all involved sites including primary tumor [10]. The pooled analysis of Epitope-HPV01 and Epitopes-HPV02 studies confirmed these data [16]. None of the 29 patients with synchronous metastases presented a disease-progression at first evaluation during DCF administration, and the ORR was reached in 26 (89.7%) patients, including 16 (55.2%) patients with a complete response.…”
Section: Locally Advanced Disease: Time To Shift the Paradigm?mentioning
confidence: 61%
“…In addition, in the whole Epitopes-HPV population of 115 patients treated with DCF, 25% of patients were still alive and disease-free at 5 years. Along with the high complete response rate, these findings suggest the potential use of DCF in neoadjuvant/adjuvant setting [16]. Anti-PD1/L1 antibodies are also potential candidates since long-lasting complete responses have been seen in chemorefractory patients in advanced SCCA [51].…”
Section: Locally Advanced Disease: Time To Shift the Paradigm?mentioning
confidence: 99%
See 2 more Smart Citations
“…An updated analysis with longer follow-up time pooled the results of the Epitopes-HPV01 and the Epitopes-HPV02 studies together. 19 A pooled analysis (n = 115) showed a median PFS of 12 months (95% CI, 10.6 to 16.0) and median OS of 50.2 months (95% CI, 26.0 to 120.0). The ORR was 87.7%, comprised of 40.7% CRs.…”
Section: Discussionmentioning
confidence: 99%